The Effect of Financial Management on Revenue for SME Actors in Gomo District South Nias, Indonesia - Hulu, Ernamawati; Hulu, Perlindungan F.; Bu’ulolo, Nanny A.; Kakisina, SophiaM. (Manunggal Halim Jaya, 2025)
From the observations, most SME actors in Gomo District, South Nias Regency still have minimal basic knowledge of good financial management. This is shown by the fact that most SME actors do not yet have financial reports, such as cash books, profit, and loss reports, and balance sheets, and have not saved for the future, invested, or taken out insurance, many of them still cannot separate personal finances from business finances. With this lack of knowledge of financial management, they cannot manage their expenses properly. Observations show that many SME actors often have difficulty reporting their financial position and calculating turnover, and business profits. The purpose of this study was to determine the Effect of Financial Management on Income for SME Actors in Gomo District, South Nias Regency. The population of this study was all Micro, Small, and Medium Enterprises in Gomo District, South Nias Regency. The results of the study showed that financial management had a significant effect on income.